NTU exam question answer forum system - Fong, Hou Jun (Nanyang Technological University, 2020)
Forum systems are becoming increasingly popular in recent years. These forum systems provide a platform for users all over the world to discuss about topics ranging from world news, to programming algorithms and more. With these platforms being easily accessible over the internet, more users take to these forums to post their daily questions and answers, to get a different perspective on different topics. Some of these platforms include reddit.com, stackoverflow.com, mathoverflow.com and local forum hardwarezone.com.sg. This project is aimed to create a Question Answer forum system, with an intention to host NTU examination questions. The project will be used to understand if this is feasible, and if it serves a purpose to NTU students. As of writing, the forum will only host NTU SCSE questions. This can later be expanded to allow other schools to have questions in this server. We will also be exploring the idea of implementing machine learning into the search engine retrieval mechanism. This is aimed to retrieve questions of more relevance from a machine learning approach.